Modern drug self-medication and associated factors among pregnant women at Settat city, Morocco - Chergaoui, Samia; Changuiti, Omaima; Marfak, Abdelghafour; Saad, Elmadani; Hilali, Abderraouf; Youlyouz Marfak, Ibtissam (Frontiers in Pharmacology, 2022)
Purpose: The consumption of drugs during pregnancy without medical advice constitutes a risk for the mother and the fetus. It is a public health problem. This study aimed to assess self-medication practices among pregnant women, the most used medicines, and factors associated with this practice. Methods: A cross-sectional study was conducted using a structured questionnaire on pregnant women who were attending Settat health centers. A simple random sampling technique was used to select the study participants. Descriptive and inferential statistics were computed using the SPSS version 19. Results: Among 364 pregnant women, 118 (32%) practiced self-medication in modern medicine. Paracetamol was the most used medication, and nausea and vomiting were the most frequent symptoms reported by self-medicated pregnant women. Multivariate logistic regression analysis showed that women over 30 years old were four-fold more likely to practice self-medication than the other groups [AOR: 4.19; 95% CI (1.80–9.77)]. Similarly, unemployed women [AOR: 3.93; 95% CI (0.80–19.23)], those in third trimester [AOR: 2.63; 95% CI (1.29–5.36)], multiparous [AOR: 6.03; 95% CI (3.12–11.65)], without chronic illness [AOR: 2.84; 95% CI (1.26–6.41)], without therapeutic treatment [AOR: 10.1; 95% CI (2.81–37.03)] and who have attended ANC at least once, were more likely to practice self-medication than the other groups. Conclusion: The prevalence of modern drug self-medication among pregnant women in Morocco is classified as lower. Health professionals can exert positive pressure through education and information provided during ANC about OTC medications to significantly reduce the rate of self-medication.